Comparison of Quality of Life in Bradycardia Patients with Permanent Pacemaker Implantation for Less Than One Year and More Than One Year at Dr. Soetomo General Hospital - Julario, Rerdin; Djuari, Lilik; Anudya Kartika Ratri; Ezekiel, Valiant (Cardiovascular and Cardiometabolic Journal (CCJ), 2026)
Abstract: Bradycardia is a condition in which the heart rate slows to below 50–60 beats per minute. Although it may occur physiologically in athletes and the elderly, symptomatic bradycardia with dizziness, chest pain, or loss of consciousness requires proper treatment. Permanent pacemaker implantation is one of the main therapies for severe bradycardia. The intent of this study is to compare the quality of life (QoL) of bradycardia patients with permanent pacemakers who have used the device for less than one year and more than one year. Material and Methods: This observational study uses a cross-sectional design. A total of 47 patient samples were collected from RSUD Dr. Soetomo, Surabaya, during 2023–2024. Data were obtained using the Short Form - 36 (SF-36) questionnaire, that includes eight Quality of life domains , and analyzed with SPSS using independent sample t-tests and Mann-Whitney U tests to determine the mean differences between the two patient groups based on pacemaker duration. Results: In general, permanent pacemaker implantation improves several aspects of quality of life, particularly social functioning and mental health. However, not all domains showed significant improvement. Patients with pacemaker exceeding one year exhibited a modest decrease in vitality and mental health scores. Independent sample t-tests and Mann-Whitney U tests indicated no significant differences between the two groups in every domain (p > 0.05). Conclusion: The study shows that the duration of pacemaker use does not always significantly correlate with improved QoL, but continuous medical care and adequate patient support effectively help maintain stable physical, psychological, and social well-being over time. -- Highlights: 1. This study finds that quality of life remains comparable between bradycardia patients with shorter and longer durations of permanent pacemaker use, suggesting early stabilization after implantation. 2. The findings indicate that sustained clinical follow-up, patient adaptation, and device effectiveness may help maintain consistent physical and psychosocial well-being over time.